Exposure to high nitrogen triggered a genotype‐dependent modulation of cell and root hydraulics, which can involve aquaporin regulation. Issue 1 (17th February 2022) - Pou, Alicia; Hachez, Charles; Couvreur, Valentin; Maistriaux, Laurie C.; Ismail, Ahmed; Chaumont, François
Abstract: Root nitrogen acquisition has been proposed to be regulated by mass flow, a process by which water flow brings nutrients to the root surface, depending on a concerted regulation of the root hydraulic properties and stomatal conductance. As aquaporins play an important role in regulating transcellular water flow, we aimed at evaluating the short‐term effect of high nitrogen (HN) availability on the dynamics of hydraulic parameters at both the root and cell level and the regulation of aquaporins. The effect of short‐term HN (8 mM NO3 − ) treatment was investigated on 12 diverse 15‐day‐old maize genotypes. Root exposure to HN triggered a rapid (<4 h) increase in the root hydraulic conductivity ( L pr ) in seven genotypes while no L pr variation was recorded for the others, allowing the separation of the genotypes into two groups (HN‐responsive and HN‐nonresponsive). A remarkable correlation between L pr and the cortex cell hydraulic conductivity ( L pc ) was observed. However, while differences in gas exchange parameters were also observed, the variations were genotype‐specific and not always correlated with the root hydraulic parameters. We then investigated whether HN‐induced L pr variations were linked to the activity and regulation of plasma membrane PIP aquaporins. While some changes in PIP mRNA levels were detected, this was not correlated with the protein levels. On the other hand, the rapid variation in L pr observed in the B73 genotype was correlated with the PIP protein abundance in the plasma membrane, highlighting PIP posttranslational mechanisms in the short‐term regulation of root hydraulic parameters in response to HN treatment.